Plant viral vectors: an strategy for transient expression of recombinant proteins in plants - Formoso, Rafaela; Vighi, Isabel Lopes; Galli, Vanessa; Pinto, Luciano da Silva (Conjecturas, 2022)
Plants have been studied as bioreactors for over 30 years. Their advantages over other expression methods arouse interest in this heterologous protein expression system. Over the years, several methods of plant transformation were developed, and among them, the transient expression system - that occurs temporarily and without integration into the host genome. The use of viral vectors for this type of expression stands out, and the viral genome can be “full-length” or “deconstructed”. Some genome modifications in the “deconstructed” form help searching for efficient protein expression, and several types of viruses are studied to develop these vectors. This review reports different types of viral vectors, especially those particularly suitable for the development of effective vectors of fast and high yield recombinant protein production, based on Tobamoviruses, Potexviruses, Geminiviruses and Comoviruses.